Application of screw-retained and cement-retained implant supported fixed restorations: A case report - Medojević Aleksandar; Jovanović-Medojević Milica; Nejković Đorđe (Serbian Medical Society - Dental Section, Belgrade, 2012)
Implantology has become an important therapeutic procedure that allows complete aesthetic and functional rehabilitation of the oro-facial system in edentulous patients. Implant supported prosthetic restorations can be fixed in two ways, by cement or screws. Both techniques have advantages and disadvantages and their selection depend on situation in patient's mouth. The aim of this study was to describe complete process of prosthetic rehabilitation in an edentulous patient, from pre-implant preparation, through implant placement and fixation of final restoration on implants. In this case report, one ceramo-metal bridge was fixed by screws in the lower jaw while the other one was fixed using glass-ionomer cement in the upper jaw. After bone augmentation and time necessary for its osseointegration (6 to 8 months), 16 implants were placed in both jaws. Eight weeks after the implant placement, final prosthetic rehabilitation was achieved by cementation of one ceramo-metal bridge in the upper jaw using glass ionomer cement and fixation of the second bridge with screws in the lower jaw. To achieve successful implant supported prosthetic rehabilitation, the treatment protocol must be followed from the beginning to the end of the therapy.